Territorialidades em contradição na escola Santo Antônio no município de Agudo - RS - Dal Ongaro, Marisa (2016)
This dissertation aims to discuss the contradictions between the reality of educating and teaching practices of educators, found in the process of teaching and learning at school in the field: Municipal School of Education Elementary Santo Antonio do Agudo-RS municipality. For this, a qualitative research was conducted on-site observation, semi-structured interview and questionnaire the families of students. Therefore, we sought to reflect on the importance of rural education, historical knowledge and territory then highlighting the dynamics in these knowledge and relating to the inclusion of environmental issues in the teaching-learning process, and the theory of Paulo Freire as guiding. Additionally, this work also presents some theoretical reflections about the construction and reconstruction of the territory in the farmer's perspective. It is considered that, in order to have a chance of resistance to agribusiness pressure, to which the class is submitted, it is necessary to diversify the property in order to achieve self-sufficiency.